“Pojok Belajar” Sarana Peningkatan Minat Belajar Bahasa Inggris Pada Anak Usia Sekolah Dasar di Desa Kotaraja - Nisfawatil Itsnaeni; Siti Namiroh; Titin Nopita; Marhamah; M. Taufik Hidayat; M. Tamzil Amrol Aen; Fathurrahman Hadi; Fahrur Rozi; M. Robi Antomi (STAI Al-Amin Gersik Kediri Lombok Barat-NTB, 2025)
The COVID-19 pandemic has changed the learning landscape around the world, including in Indonesia. Online learning has become a solution to ensure the continuity of the teaching and learning process. However, online learning also faces various challenges, especially in increasing students' interest in learning, especially for English subjects in elementary school children. This community service aims to increase the interest in learning English in elementary school children in Kotaraja Village through the “Learning Corner” program. The methods used in this community service are training, mentoring, and evaluation. The results of this service show an increase in interest in learning English in elementary school students in Kotaraja Village after participating in the “Learning Corner” program. The conclusion of this service is that the “Learning Corner” program is effective in increasing the interest in learning English in elementary school children in Kotaraja Village.